The dyslexia susceptibility KIAA0319 gene shows a specific expression pattern during zebrafish development supporting a role beyond neuronal migration. Issue 16 (16th April 2019) - Gostic, Monika; Martinelli, Angela; Tucker, Carl; Yang, Zhengyi; Gasparoli, Federico; Ewart, Jade‐Yi; Dholakia, Kishan; Sillar, Keith T.; Tello, Javier A.; Paracchini, Silvia
Abstract: Dyslexia is a common neurodevelopmental disorder caused by a significant genetic component. The KIAA0319 gene is one of the most robust dyslexia susceptibility factors but its function remains poorly understood. Initial RNA‐interference studies in rats suggested a role in neuronal migration whereas subsequent work with double knock‐out mouse models for both Kiaa0319 and its paralogue Kiaa0319‐like reported effects in the auditory system but not in neuronal migration. To further understand the role of KIAA0319 during neurodevelopment, we carried out an expression study of its zebrafish orthologue at different embryonic stages. We used different approaches including RNAscope in situ hybridization combined with light‐sheet microscopy. The results show particularly high expression during the first few hours of development. Later, expression becomes localized in well‐defined structures. In addition to high expression in the brain, we report for the first time expression in the eyes and the notochord. Surprisingly, kiaa0319‐like, which generally shows a similar expression pattern to kiaa0319, was not expressed in the notochord suggesting a distinct role for kiaa0319 in this structure. This observation was supported by the identification of notochord enhancers enriched upstream of the KIAA0319 transcription start site, in both zebrafish and humans. This study supports a developmental role for KIAA0319 in the brain as well as in other developing structures, particularly in the notochord which, is key for establishing body patterning in vertebrates. Abstract : The kiaa0319 gene shows a specific pattern of expression during the early phases of zebrafish development. In the first 12 hr of development it is strongly expressed in the (a) brain and (b) body. Later, it is expressed in specific structures such as the (c) eye and (d) notochord.